Improving Nursing Home Disaster Readiness Through Implementation Science. - Bell, Sue Anne; Inloes, Jennifer B.; Donnelly, John; Wasserman, Michael; Wyte-Lake, Tamar (Journal of the American Medical Directors Association, 2024)
As large-scale disasters continue to become increasingly common worldwide, nursing homes, whose residents are more vulnerable to disaster-related health and psychosocial shocks, and their staff, are carrying progressively more responsibility for health care readiness practices. Implementation science is a research discipline that seeks to improve uptake of evidence-based practices, such as health care readiness planning, and thus has potential to improve nursing home care delivery during and after disasters. We describe the limited field of existing evidence-based strategies in the peer-reviewed literature that seek to advance health care readiness in the nursing home setting and illustrate how implementation science can better support health care readiness planning for nursing homes. We rest on 3 main themes: (1) implementation science frameworks can strengthen nursing home staff engagement around health care readiness; (2) implementation science can support tailoring of emergency preparedness plans to individual nursing homes' unique needs; and (3) implementation science can advance the integration of nursing homes into local, state, and federal health care readiness planning initiatives. Finally, research is urgently needed to both generate and disseminate implementation strategies that increase uptake of evidence-based health care readiness practices in the nursing home setting.